Implementasi Metode Certainty Factor Dalam Diagnosa Penyakit Gigi - Yuza Reswan; Pahrizal Pahrizal; Khairullah Khairullah; Mat Agus (Jurnal Media Infotama, 2024)
This study aimedd to build an application program that can aid plant experts provide knowlwdge in the form of an expert system.so it can be employed to treat diseases of the teeth. The system can forecast diseases.the method usedd was the expert system which is built using a certainty value called certainty factor. The resulting values can be utilized to infer the types of diseases and pests on the grapes. The results achieved from this study are the implementation of the Certainty Factor method in the diagnosis of dental disease. The conclusion of this study is to produce a website-based expert system that can help doctors diagnose dental diseases based on the symptoms caused.